Social and Spiritual Communication of Togel Gamblers in Surabaya City - Syaifudin Zuhri; Moh. Moefad, Agoes; Maulidatus Syahrotin Naqqiyah (Mediakita, 2025)
Surabaya, one of Indonesia's metropolitan cities, cannot be said to be free from the phenomenon of lottery gambling in its community. In addition to legality and economic problems, lottery gambling in Surabaya also contains very complex social and spiritual dimensions. This study explores social and spiritual communication among lottery gamblers in Surabaya. This study employs a qualitative descriptive research method and an ethnographic approach. James Fowler's spiritual transformation theory is applied to view the social-spiritual communication of lottery gamblers in Surabaya. Based on the study's findings, in a social context, lottery gamblers can form very close solidarity. However, on the other hand, this attachment also triggers addiction and social conflict. Regarding social spirituality, Surabaya lottery gamblers have a unique pattern of using symbols and codes to interact. In addition, Surabaya lottery gamblers firmly believe in dreams, rituals, and prayers before starting to bet. This shows that although gambling is prohibited by religion and the state by law, lottery gamblers remain optimistic by seeking spiritual legitimacy in various ways, visiting sacred places, visiting shamans, interpreting dreams, and even linking social events with lottery numbers.